The Analysis of The Work Environmental and Organizational Cultural Impact on The Performance and Implication of The Work Satisfaction - Sunarsi, Denok (Jurnal Ilmiah Ilmu Administrasi Publik, 2019)
This study aimed at analyzing the impact of the work environment and organizational culture on its performance and implications for the satisfaction of elementary school teachers in the region ofÂ  Bogor - West Java. The method of data analysis uses quantitative decryptive analysis techniques in which its population is an entire elementary school teacher in the region of Bogor - West Java which the total are 18,653. While on collecting sample, the writer used the slovin formula with a 10% error rate in which a 99.47 collected amount of samples would be 100 responders. Research results confirm that (1). The work environment has a partial positive and significant effect on the performance; (2). Organizational culture has a partial positive and significant effect on performance; (3). The work environment and organizational culture simultaneously have a positive and significant impact on the performance; (4). The work environment has a partial positive and significant impact on work satisfaction; (5). Organizational culture has a partial positive and significant impact on work satisfaction; (6). Partial performance has a positive and significant impact on work satisfaction. (7). Work environment, an organizational culture and performance simultaneously have a positive and significant impact on performance.